INTELLECTUAL FREEDOM AND CENSORSHIP IN THE EYES OF NIGERIAN LAW (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Intellectual freedom according to Article 19 of United Nations Universal Declaration of Human Rights is the right to freedom of thought and of expression of thought. Intellectual freedom guarantees everyone the right to freedom of opinion and expression. This right includes the freedom to hold opinions without interference and to seek, receive and impact information and ideas through any media and regardless of frontiers. Thus intellectual freedom encompasses the freedom to hold, receive and disseminate ideas. Whereas censorship is the suppression of ideas and information that individuals, groups or government officials find objectionable or dangerous. Censors usually achieve this through state powers via public institutions such as schools, libraries, information centres among others. Through the instrumentality of the law, such public institutions are prohibited from making censored materials easily accessible to the public or to targeted audience. This paper x-rayed those international and Nigerian laws that encourage or impinge access to information for one and all in Nigeria. It also made recommendations that will enhance easy flow of information to all information seekers in Nigeria.